2009
DOI: 10.1007/s11270-009-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Multi-criteria Analysis of Air Pollution with SO2 and PM10 in Urban Area Around the Copper Smelter in Bor, Serbia

Abstract: This work presents the results of 4 years long monitoring of concentrations of SO2 gas and PM10 in the urban area around the copper smelter in Bor. The contents of heavy metals Pb, Cd, Cu, Ni, and As in PM10 were determined and obtained values were compared to the limit values provided in EU Directives. Manifold excess concentrations of all the components in the atmosphere of the urban area of the townsite Bor were registered. Through application of a multi-criteria analysis by using PROMETHEE/GAIA method, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…The results on measurement and modeling of SO2 distribution in air, at different location in city of Bor, resulting from the smelter plant operation, are published by the project group from TF Bor, in Savić et al, 2013;Nikolić et al, 2010b andĐorđević et al, 2013. The average monthly SO2 concentrations at particular measuring locations, which were the part of the monitoring system of the town of Bor in 2011, are shown in Source: Đorđević et al, 2013 While, the highest contents of some heavy metals were found in the samples taken from the different locations (Figure 2) near to the town center (Table 1).…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results on measurement and modeling of SO2 distribution in air, at different location in city of Bor, resulting from the smelter plant operation, are published by the project group from TF Bor, in Savić et al, 2013;Nikolić et al, 2010b andĐorđević et al, 2013. The average monthly SO2 concentrations at particular measuring locations, which were the part of the monitoring system of the town of Bor in 2011, are shown in Source: Đorđević et al, 2013 While, the highest contents of some heavy metals were found in the samples taken from the different locations (Figure 2) near to the town center (Table 1).…”
Section: Research Resultsmentioning
confidence: 99%
“…This technology is based on classical pyrometallurgy, with smelting in reverberatory furnaces and a relatively low degree of sulfur dioxide (SO2) gas utilization (< 50 %) for the production of sulfuric acid. This lead to emission of large quantities of SO2, in the concentration much above prescribed maximal limited values (MLV), accompanied by emission of the toxic airborne particle matter (PM10), , as well as aero-sediments even larger than the PM10 particles, containing increased quantity of heavy metals (Nikolić et al, 2010b). This lead to degradation of a huge soil area, a huge volume of the soil waste generated over the years and pollution of underground and surface waters.…”
Section: Environmental Consequences Of One Century Of Copper Productionmentioning
confidence: 99%
“…They include "site-by-site" method which is suitable for identification of monitors which could be relocated [3], "bottom-up" method which analyses phenomena that lead to increased concentrations of pollutants [4] and network optimisation using different analysis techniques including statistical methods, principal component analysis and cluster analysis, for identification of redundant measuring points [5,6]. Many authors also use different methods of multi-criteria analysis: combined with other methods [7÷14] or independently [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In one of the regions of Spain, in the period 2004 -2007, SO 2 concentrations ranged up to 100 μgm -3 (Santacatalina et al, 2011). In the vicinity of the copper smelter in Bor, Eastern Serbia, in the period [2005][2006][2007][2008], in the urban part of the city, maximum monthly average SO 2 concentrations were recorded in the range of 500-2000 μgm -3 (Nikolić et al, 2010). In the period 2000-2008, the episodes occurred with a daily average values in the range of 5000 -8000 μgm -3 in this region (Dimitrijević et al, 2008), when the smelter was stopped after intervention of the state for a few days because of the high toxicity of gas, and then continued to work with the same technical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In the technology of copper production in this company, since 1975 to date, important improvement at the stage of melting, refining gas and production of H 2 SO 4 has not been done. Since 2003, immission of pollutants was monitored at eight measuring points (Nikolić et al, 2010), and after 2010 only at three measuring points, with limited measurement range and transparency of data controlled by the government, and at the two measuring points with the internal character data. In the period 2009-2011, there were episodes of extremely high concentrations of SO 2 with over 9000 μgm -3 , with fatal consequences for the bees and agricultural crops.…”
Section: Introductionmentioning
confidence: 99%